Critical issues in social studies research for the 21st century - Stanley, William B. (Emerald Publishing Limited : Information Age Publishing, 2001)
The authors of the nine other chapters in this book have struggled with the issues discussed above in several different ways. The chapter authors represent a wide range of views and expertise within the field of social stud-ies. Some have been leading social studies scholars for three or four decades. Other authors represent new voices that have begun to shape the direction social studies will take in the future. The topics examined here include the debate over how to define social studies, social studies and the impact of the standards/accountability movement, the contextual con-straints/ restraints on teaching social studies, education for democracy, rationales for teaching history, multicultural education, global education, social studies and educational technology, and the nature and effectiveness of social studies research.
Keywords: Social sciences -- Research.; Social sciences -- Study and teaching.; Social Science -- Research.; Social and ethical issues.; Social research and statistics.; elektronické knihy; electronic books